Upaya Meningkatkan Kemampuan Kognitif Melalui Strategi Ice Breaking Pada Anak Usia 5-6 Tahun - Adindan, Wiwik; Adawiyah, Robiatul; sapira, Mutia (LPPM STAI La Tansa Mashiro, 2025)
Is an important process in the formation of thinking skills, which is influenced by various internal and external factors, and takes place through certain stages according to the child's age.This study aims to: (1) Determine the condition of cognitive development of children aged 5-6 years at RA Mutiara before the implementation of the ice breaking strategy, (2) Determine the condition after the implementation of the strategy, and (3) Assess the effectiveness of the ice breaking strategy in improving children's cognitive development. This study uses a qualitative approach with the Classroom Action Research (CAR) method, where the research subjects are students of group B2 RA Mutiara for the 2024/2025 Academic Year. Data collection was carried out through observation, interviews and documentation during the study. This study shows that there is an increase in the cognitive abilities of early childhood after implementing the ice breaking strategy during cycle II, cycle I with two meetings and cycle II with one meeting. The results of the percentage of cognitive abilities in children from the beginning of the pre-cycle reached a class average of 30% then in cycle I meeting I the class average was still 30%, cycle I at meeting II the class average increased to 40% then in cycle II increased to 60%. Thus, from the results of the percentage, it shows that the ice breaking strategy can improve cognitive development in children aged 5-6 years. As has been stated in the results of the analysis, this study can be said to be successful in accordance with the achievement of the success criteria, namely Developing According to Expectations (BSH) with the percentage of average cognitive abilities of the class reaching 43%.